2013
DOI: 10.1371/journal.pone.0076667
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Extra-Pancreatic Trypsin 3 Secretion Promotes Cell Proliferation and Survival in Esophageal Adenocarcinoma

Abstract: Trypsin or Tumor associated trypsin (TAT) activation of Protease-activated receptor 2 (PAR-2) promotes tumor cell proliferation in gastrointestinal cancers. The role of the trypsin/PAR-2 network in esophageal adenocarcinoma (EA) development has not yet been investigated. The aim of this study is to investigate the role of trypsin/PAR-2 activation in EA tumorogenesis and therapy. We found that esophageal adenocarcinoma cells (EACs) and Barrett’s Metaplasia (BART) expressed high levels of type 3 extra-pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…43 Consistently, we found that ECA-109 and TE-1 cells are more resistant to 5-Fu than other chemosensitive esophageal cancer cells such as OE19 and OE33 cells (Fig. S3A) [44][45][46] and that 5-Fu induces prosurvival autophagy, and caspase-independent and autophagy-associated cell death (Fig. 5D and 6C).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…43 Consistently, we found that ECA-109 and TE-1 cells are more resistant to 5-Fu than other chemosensitive esophageal cancer cells such as OE19 and OE33 cells (Fig. S3A) [44][45][46] and that 5-Fu induces prosurvival autophagy, and caspase-independent and autophagy-associated cell death (Fig. 5D and 6C).…”
Section: Discussionsupporting
confidence: 70%
“…S3A), which was consistent with previous reports. 44,45 Unexpectedly, these cells were more 5-Fu-resistant than other chemosensitive cells such as OE19 (IC 50 = 3.03 μg/ml) and OE33 (IC 50 = 1.24 μg/ml), 46 implying that ECA-109 and TE-1 cells were 5-Fu-resistant. A recent study showed that 5-Fu-induced cell death in chemoresistant esophageal cancer cells is apoptosis-independent, and that autophagy exerts a protective effect.…”
Section: -Fluorouracil Induces Protective Autophagy In Esophageal Camentioning
confidence: 89%
“…In addition to the well-known role of PAR-2 in the primary proliferation of various cancer cells [2,3], including pancreatic cancer [4], the results presented highlighted convincingly the importance of stromal host receptors relative to local progression in the orthotopic pancreatic cancer model. The authors recorded an increase in the average volume of primary tumours in wild-type animals compared with PAR-2 −/− knockouts.…”
supporting
confidence: 59%
“…One study has proposed that PRSS3 serves as a robust growth factor for HT29 colon cancer cells via the activation of PAR2 and the downstream phosphorylation of ERK, which results in cell proliferation [26]. Another significant study suggested that secreted PRSS3 acts on the PAR2 receptor as an autocrine survival signal; targeting this axis increased sensitivity to chemotherapy in esophageal adenocarcinoma cell lines [27]. Similarly, PRSS3 regulation of cellular adhesion and proliferation mediated by PAR2/G-protein signaling has been reported in other malignancies, such as breast cancer and gastric cancer [28,29].…”
Section: Discussionmentioning
confidence: 99%